Evaluating the role of graft angle on cerebral hemodynamics following direct cerebral bypass for moyamoya disease - Cheng Peng; Ephraim W. Church; Melissa C. Brindise (PLoS ONE, 2026)
Direct cerebral bypass is a key treatment for moyamoya disease (MMD). This surgery grafts a donor vessel onto a recipient cerebral artery to boost blood flow to hypoperfused brain regions. Unlike coronary bypass, which restores downstream flow around a blockage, cerebral bypass for MMD reverses flow in the recipient vessel to perfuse the upstream network. Surgical decisions—such as donor vessel choice and anastomosis angle—significantly affect graft hemodynamics and outcomes. Yet these choices still rely on neurosurgeons’ experience, lacking quantitative guidance. This study addresses that gap by examining how anastomosis angle shapes post-surgical perfusion and wall shear stress. We created idealized cerebral bypass models with graft angles of 30°, 60°, and 90°. Each model’s flow field was assessed under varying inflow and graft-flow combinations using computational fluid dynamics. The 30° angle produced the strongest reverse flow but also the largest WSS imbalance, potentially driving long-term complications. The 60° angle achieved adequate reverse flow with a more uniform WSS profile, making it the most favorable. Overall, our results show graft angle must be carefully considered in cerebral bypass planning.